Uma análise dos fatores cognitivos mensurados pelo Exame Nacional do Ensino Médio (ENEM) - Cristiano Mauro Assis Gomes (2005)
This research analyses the relationship between the competences of Exame Nacional do Ensino Médio (ENEM) and the cognitive abilities of psychometric. Validation studies of Carroll Tree Stratum Model were conducted through application to federal high school students of 45 tests of the Educational Testing Service Kit of Referenced-Factor Cognitive Tests and application of ENEM objective instrument of 2001. The cognitive tests applied were translated and adaptated for the context of research participants, and validated about your function like cognitive reference. The objective of identify the dimensions of Carroll Tree Stratum Model and the ENEM Cognitive Model was conducted through the many exploratory factorial analysis approaches. The dimensions was extracted through the Principal Axis Factoring and validated through parallel analysis by permutation, superior to engeinvalue-rather-than- one and the Cattell Scree Test. The factors were rotated through the oblimin approach. Results indicated the presence of five secondary factors of Tree Stratum Model, Crystallized Intelligence (Gc), Memory (Gy), Fluency (Gr), Visual Ability (Gv) and Cognitive Speed (Gs) and the occurrence of tertiary factor of Tree Stratum Model, a general cognitive ability (g). The participants scores of ENEM instrument of 2001 didnt indicate the abilities and competences of ENEM Cognitive Model but indicated the existence of one Scholar General Competence, of second level, and the Verbal Competence and the Quantitative Competence, of first level. The cognitive factors that best related with the ENEM dimensions were Crystallized Intelligence, follow to Factor General (g) and the Visual Ability (Gv). Through the evidences find in this research it is possible that the Factor General (g) extracted could be the same the Fluid Intelligence (Gf), like think Undheim and Gustafsson. The strong relationship between some cognitive factors and the dimensions of ENEM demonstrated one connection between the intellectual architecture of psychometric and the academic achievement, and these connection open questions about the role of teaching the intelligence modalities in the Brazilian education.